Strategi Penguatan Kinerja Karyawan: Dampak Kompensasi dan Motivasi Terhadap Disiplin Kerja Sebagai Mediator - Al-Faqih, Annas; Nuraeni, Nuraeni (Dinasti Research, 2025)
This study aims to analyze the effect of compensation and motivation on employee performance with work discipline as a mediating variable at PT Sustraco Adikreasi. The research employed a quantitative approach using a census method involving 40 respondents. Data were collected through questionnaires and analyzed using SPSS version 20 with multiple linear regression and Sobel test. The results showed that: (1) compensation does not have a significant effect on employee performance, (2) motivation has a positive and significant effect on employee performance, (3) compensation has a positive and significant effect on work discipline, (4) motivation has a positive and significant effect on work discipline, (5) work discipline has a positive and significant effect on employee performance, (6) work discipline significantly mediates the effect of compensation on employee performance, but (7) work discipline does not significantly mediate the effect of motivation on employee performance. These findings highlight the crucial role of work discipline as a mediator in the relationship between compensation and performance, but not in the relationship between motivation and performance.